Recurrent unilateral peripheral facial palsy in a patient with an enlarged styloid process. Issue 3 (24th December 2018) - Péus, Dominik; Kollias, Spyros S.; Huber, Alexander M.; Huber, Gerhard F.
Abstract: Background: Recurrent peripheral facial paresis is a rare symptom that may be caused by multiple pathologic conditions. Methods: We report a case of recurrent peripheral facial palsies caused by an ipsilateral enlarged styloid process. A surgical excision of the process was performed. Results: The treatment was well tolerated. Postoperatively, no further recurrent paresis was observed. Conclusion: To the best of our knowledge, this is the first case study of an enlarged styloid process with facial paresis. A detailed workup, including imaging, should be performed in cases with recurrent facial paresis and/or cases with a history of trauma and facial paresis and, of course, to exclude a neoplastic etiology.